Biodigestão anaeróbica da fração orgânica de resíduos sólidos urbanos consorciado com glicerina - Rempel, Neuri (Universidade do Vale do Rio dos Sinos, 2014)
The energetic use of the biodegradable fraction of Municipal Solid Waste (MSW) in the form of biogas is one of the alternatives to minimize the social and environmental impacts caused by the disposal of this waste. Anaerobic digestion under controlled conditions, aiming the maximum yield of biogas, is promising alternative, especially when conducted with the addition of others organic wastes with high potential for biogas generation, such as glycerin. Glycerin is a subproduct of biodiesel production and carbon percentage above 90%, making it an excellent co-substrate for anaerobic digestion. This research evaluated the generation of biogas in pilot scale, using the organic fraction of the MSW post-treadmill screening of São Leopoldo/RS, with the increase of glycerin on the mass of residue added to the digester. A 50L reactor with intermittent agitation and controlled temperature (~35°C) has been used. The increase of glycerin made possible the raise up to 30% in the volume of generated biogas, besides anticipate within 10 days maximum biogas production compared to the process only with MSW. The gradual decrease in pH, the high C:N ratio in digested material and the addition of NaOH to control the pH, indicate that the percentage of glycerin added, under the conditions of this study may have been high, requiring further investigation to reach proper volume. The results indicate the necessity to determine the optimal percentage of glycerin to be used, which was not possible in this study. Intermittent agitation, maintaining the pH close to 7.5 and Maximum Solids Retention Time of 25 days, were the main parameters observed to optimize the generation of biogas, in the conditions of this study. The mean volume of biogas produced was 44m3/ton of MSW with minimum and maximum values of 30 m3/ton and 60 m3/ton MSW, respectively.
Anaerobic digestion of the organic fraction of urban solid waste consortium with glycerin
Keywords: Biogás; Digestão anaeróbia; Resíduos sólidos urbanos; Biodigestor; Glicerina; Biogas; Anaerobic digestion; Municipal solid waste; Digester; Glycerin; ACCNPQ::Engenharias::Engenharia Civil